Strategic cultures of philanthropy: English universities and the changing geographies of giving - Adam Warren; Michael Hoyler; Morag Bell (2014)
UK universities are receiving record amounts of funding from private philanthropists. In 2013, it was reported that, for the first time, UK Higher Education Institutions (HEIs) obtained more major donations from philanthropic sources than any other cause. Three decades of increased neoliberalism and internationalisation of the Higher Education (HE) sector, together with a decline in state funding, have heightened the imperative for English universities in particular to intensify engagement with potential private donors. The UK government, via its Matched Funding Scheme (MFS) 2008-2011, sought to incentivise giving to HEIs in England. Universities have thus been encouraged to grow a 'culture' of philanthropy. Yet, there has been limited investigation by geographers into the impact of private donations on UK HEIs.In this paper, we undertake a critical examination of the official publications of 17 diverse English HEIs which participated in the MFS 2008-2011. Particular attention is paid to the differentiated levels of participation by universities with the MFS and the ways in which donations were represented in their public documents. We argue that diverse cultures of HEI engagement with philanthropic giving are critically linked to their: location in conventional institutional hierarchies; integration in professional knowledge networks; and ability to mobilise strategic connections across geographical scales. In doing so, we advance theoretical work on the role of philanthropic giving in reconfiguring contemporary geographies of HE. © 2014 Elsevier Ltd.